Psychosocial risks emerged from COVID-19 pandemic and workers’ mental health - Koren, Helena; Milaković, Marina; Bubaš, Marija; Bekavac, Petra; Bekavac, Barbara; Bucić, Lovro; Čvrljak, Jelena; Capak, Magdalena; Jeličić, Pavle (Frontiers in Psychology, 2023)
This paper examines the impact of work in a pandemic context on workers' mental health. Psychosocial risks have always been a challenging aspect of workplace health and safety practices. Moreover, the COVID-19 pandemic has affected workplaces in all sectors causing unexpected changes in work organization and working conditions, leading to the emergence of new psychosocial risks for health and well-being of workers. This mini-review aims to identify the main work stressors during pandemic period and related mental health problems to suggest recommendations and adjust health and safety practices regarding workplace mental health. A literature search has been performed using MEDLINE/PubMed, ResearchGate and Google Scholar databases, selecting articles focusing on work-related stressors and workers' mental health problems related to the pandemic. Specific psychosocial risks have been identified, including fear of contagion, telework-related risks, isolation and stigmatization, rapid digitalization demands, job insecurity, elevated risk of violence at work or home, and work-life imbalance, among others. All those risks can lead to elevated levels of stress among workers and affect their mental health and well-being, especially in terms of psychological distress, anxiety, and depression. As one of the social determinants of health, the workplace has an important and moderating role in workers' health. Therefore, in the pandemic context more than ever health protection practices at the workplace should be devoted to mental health problems. Recommendations provided in this study are expected to contribute to workplace practices to preserve and promote workers' mental health.